1997
DOI: 10.1021/bi970846o
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Activation of Phosphatidylinositol-Specific Phospholipase C:  Specific Phospholipid Binding Anchors the Enzyme to the Interface

Abstract: Phosphatidylinositol-specific phospholipase C (PI-PLC) from Bacillus thuringiensis exhibits 'interfacial activation' toward the water-soluble substrate myo-inositol 1,2-(cyclic)phosphate [Zhou et al. (1997) Biochemistry 36, 347-355]. The activation of PI-PLC enzyme is optimal with PC or PE interfaces. NMR experiments (TRNOE and 31P line width analyses) were carried out to investigate the interaction of PI-PLC with activator amphiphiles. These studies showed that the enzyme had high affinity for phosphatidylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
108
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(112 citation statements)
references
References 27 publications
3
108
1
Order By: Relevance
“…In so doing they provide a specific recognition motif for the head- groups of zwitterioinic phospholipids. Bacillus PI-PLC is activated by PC (10), in large part by enhancing vesicle binding (25). The G helix region of Bacillus PI-PLCs has several Tyr residues that could form a sandwich or cage around a choline group (22,28), but how and whether PC binds to this box was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In so doing they provide a specific recognition motif for the head- groups of zwitterioinic phospholipids. Bacillus PI-PLC is activated by PC (10), in large part by enhancing vesicle binding (25). The G helix region of Bacillus PI-PLCs has several Tyr residues that could form a sandwich or cage around a choline group (22,28), but how and whether PC binds to this box was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, proteins specific to the anionic phospholipid phosphatidylserine (PS) 2 may coordinate Ca 2ϩ ions for PS binding using conserved loop motifs as observed in annexin V (5) or directly bind PS via C2 domains as in coagulation factor V (6) and lactadherin (7) where polar side chains allow specific recognition of PS. The affinity of the proteins for the membrane may be further modulated by insertion of hydrophobic and aromatic amino acids into the bilayer (5,6,8) and/or multivalent interactions (3) via domain repeats (9) or specificity for more than one type of lipid (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Around the barrel rim, there are regions where hydrophobic side chains are exposed to solvent. The structural similarity of the bacterial PI-PLC to the mammalian catalytic domain and similar kinetic features (12)(13)(14) suggest that the smaller enzyme can provide a simple model for understanding how different interfaces modulate catalysis.Previous work has shown that the PI-PLC from Bacillus cereus or Bacillus thuringiensis not only prefers micellar to monomeric substrate (15) but is also activated by binding to phosphatidylcholine (PC) interfaces (2,16,17). The binding has an allosteric effect on the enzyme, since it increases k cat and decreases K m for hydrolysis of the soluble substrate cIP.…”
mentioning
confidence: 99%
“…Previous work has shown that the PI-PLC from Bacillus cereus or Bacillus thuringiensis not only prefers micellar to monomeric substrate (15) but is also activated by binding to phosphatidylcholine (PC) interfaces (2,16,17). The binding has an allosteric effect on the enzyme, since it increases k cat and decreases K m for hydrolysis of the soluble substrate cIP.…”
mentioning
confidence: 99%